(untitled) (Baghdad Science Journal, 2025)
The study involved 45 male and 45 females of diabetic patients type- ?? aged from 40-69years , and with the same numbers of males and females for control , all the patients and controls were without any periodontal diseases and without any systemic disease. Diabetic patients were divided in to three groups according to the degree of periodontitis , and the inflamed gingiva of all groups of diabetic patients were treated with the dried fruits powder (crude) of medicinal plants Quercus robur , Thuja occidenalis , Terminalia chebula, Anethum graveolens , respectively and mixture. Some immunological and antimicrobial factors (IgA, Lactoferrin , Lysozyme ) , were detected in serum and saliva of diabetic patients and the controls , the results revealed that the level of IgA , Lysozyme in saliva were more than in serum of the control , and this will insure that these factors are considered to be generally protected against bacteria in the oral cavity . Also there was a significant increase at (p?0.001) especially after treatment with the mixture of medicinal plants , so that the mixture of these plants can be considered the best type in the treatment of inflamed gingiva of type –?? diabetic patients.